Behavioral testing approach to assessing noise exposure - McElree, Carrie (My University, 2023)
Objective Limited research exists on the use of clinical-based tests of auditory processing to assess central auditory function in noise-exposed individuals. The purpose of the current study was to assess central auditory function in normal-hearing young adult hunters, as well as identify clinically useful auditory processing tests to be used in the assessment of noise-exposed individuals. Methods A total of 20 normal-hearing young adults, 10 non-hunters and 10 hunters, were recruited for study. Participants underwent a comprehensive audiologic evaluation and auditory processing test battery. Tests of auditory processing assessed speech-in-noise discrimination, dichotic listening, temporal processing, monaural low redundancy, and binaural interaction. Mixed ANOVAs and t-tests were used to analyze differences in test scores between non-hunters and hunters. Results Hunters had significantly higher (poorer) audiometric thresholds at 6000 and 8000 Hz than non-hunters. Hunters also performed significantly worse on the Auditory Figure Ground (AFG) +12 and Low Pass Filtered Speech (LPFS) tests. Significant ear effects were observed on both the Competing Sentences Test (CST) and Competing Words Directed Ear (CWDE) test. Conclusions Noise exposure can impact performance on clinical tests of central auditory processing. Clinical tests of auditory processing, such as the AFG +12, CWDE, CST, and LPFS may be effective in identifying functional deficits in noise-exposed individuals. Specifically, these tests can provide clinically beneficial information that can be used to structure intervention plans, as well as hearing conservation test protocols. However, further research is warranted to truly comprehend the effect of noise on central auditory processing.
(Au. D.) -- Towson University, 2021